Indigenous Prosperity and American Conquest : Indian Women of the Ohio River Valley, 1690-1792 - Sleeper-Smith, Susan (Book collections on Project MUSE., 2018)
"What frustrated Washington was his ongoing failure to induce Indians north of the Ohio to cede their lands ... Washington had sought to pacify the Indians by abandoning the doctrine of discovery and reimbursing them for their lands. But they continued to refuse to come to the treaty table, condemned further land cessions north of the Ohio, and formed the first northwestern Indian confederacy to oppose intrusion on their homelands ... Washington had to find other means to undercut Indian resistance. Those means involved razing villages, destroying the crops, and taking hostage the women and children the warriors were trying to protect ... Washington ordered the Kentucky militia to cut a wide swath of terror though agrarian communities clustered along the Wabash. Those villages, primarily populated by women, served as the breadbasket for Indian forces. Washington believed that the destruction of these communities and the kidnapping of their women and children would force those warriors to return to their villages and abandon their resistance to Washington's forces. He had done it successfully to the Seneca during the Revolutionary War, and he planned to do it again"--Introduction